Multiple Choice Item Analysis in Indonesian Language Under Merdeka Curriculum: Analisis Soal Pilihan Ganda dalam Bahasa Indonesia Berdasarkan Kurikulum Merdeka - Nafiatuz Zukhruffah; Ahmad Nurefendi Fradana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid developments in science and technology require continuous innovation in Indonesia’s education system, including the implementation of the Merdeka Curriculum, which emphasizes flexible learning and competency-based assessment. Specific Background: In elementary education, multiple-choice tests in Indonesian language subjects play a crucial role in evaluating students’ comprehension, communication skills, and language structure mastery. Knowledge Gap: However, the quality of test items often varies, and systematic qualitative analysis of item characteristics aligned with the Merdeka Curriculum remains limited. Aims: This study aims to analyze the characteristics and quality of Indonesian language multiple-choice items for fifth-grade elementary students within the Merdeka Curriculum framework. Results: Using a qualitative phenomenological approach through questionnaires and teacher interviews, the findings indicate that most items generally function adequately but require minor revisions to improve validity, reliability, difficulty balance, discrimination power, and distractor performance, while clearer language and alignment with learning objectives are essential. Novelty: The study provides a comprehensive qualitative examination integrating cognitive level analysis, construction, language clarity, and alignment with the Pancasila Student Profile within a real school context. Implications: The results suggest that careful item construction and systematic analysis can produce more representative assessment instruments that measure students’ competencies holistically and support curriculum goals. Highlights: Most questions were acceptable but needed refinement to meet measurement standards. Language clarity and alignment with learning objectives were critical issues identified. Cognitive level distribution indicated the need for more higher-order thinking tasks. Keywords:Merdeka Curriculum; Multiple Choice Test; Item Analysis; Indonesian Language Education; Elementary Assessment